Assessing moodle-assisted e-learning for students’ concept understanding and critical thinking skills in algebra - Pahrudin, Agus; Zahra, Yustika Fatimatuz; Supriadi, Nanang; Sugiharta, Iip; Farida, Farida; Suherman, Suherman (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
Conceptual understanding and critical thinking skills are necessary for all students to help them in their learning process. This research aims to determine the effect of Moodle-assisted e-learning on (1) conceptual understanding, (2) critical thinking skills, and (3) conceptual understanding and critical thinking skills combined. This research employed a quasi-experimental design with random cluster sampling was used as the sampling technique. An algebra written test was used to collect research data. Furthermore, the researchers performed the normality test, homogeneity test, and MANOVA analysis to analyze the data. The researchers discovered that Moodle-assisted e-learning influenced students' conceptual understanding, critical thinking skills, and conceptual understanding and critical thinking skills.